Czynniki i perspektywy rozwoju polsko-niemieckiej współpracy transgranicznej po przystąpieniu Polski do Unii Europejskiej - Ładysz, Jerzy (Factors and Prospects of the Development of Polish-German Crossborder Cooperation after Poland's Accession to the European Union, 2005)
The article concerns the tendencies of development of Polish-German crossborder cooperation after Poland's accession to the European Union. Some important factors will determine these tendencies. In the next part of the article the analysis of relationship between the progress of regional integration and the development of crossborder cooperation has been used to justify the main thesis.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 269-275